Setetes Darah, Sejuta Kasih dan Harapan: Kegiatan Donor Darah Sukarela oleh Lions Club Medan Angkasa untuk Meningkatkan Ketersediaan Stok Darah di Medan - Anto, Endy Juli; Tim Lions Club Medan Angkasa; Tambunan, Ronald T. H.; Manullang, Frengky S.; Tiji, Wijaya Taufik; Fauzi, Tengku M.; Sinatra, Jadeny; Jamnasi, Juli; Siahaan, Jekson Martiar (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
Blood donation is a critical healthcare activity that saves millions of lives worldwide. This community service activity aimed to increase blood stock availability and raise awareness about voluntary blood donation through Lions Club Medan Angkasa's initiative "Setetes Darah, Sejuta Kasih dan Harapan" (A Drop of Blood, Million Love and Hope). The blood donation drive was conducted on November 26, 2023, at Manhattan Times Square 3rd floor, Medan. The activity included health screening, blood collection, and educational sessions about the importance of regular blood donation. A total of 150 voluntary donors participated in the event, successfully collecting 135 bags of blood (340cc each) after medical screening. The results showed high community participation and awareness about the importance of blood donation. This initiative demonstrates the effectiveness of community-based organizations in supporting healthcare systems and promoting voluntary blood donation culture in society.